Indigenous uses of wild and tended plant biodiversity maintain ecosystem services in agricultural landscapes of the Terai Plains of Nepal - Jessica P. R. Thorn; Thomas F. Thornton; Ariella Helfgott; Kathy J. Willis (BMC, 2020)
Abstract Background Despite a rapidly accumulating evidence base quantifying ecosystem services, the role of biodiversity in the maintenance of ecosystem services in shared human-nature environments is still understudied, as is how indigenous and agriculturally dependent communities perceive, use, and manage biodiversity. The present study aims to document traditional ethnobotanical knowledge of the ecosystem service benefits derived from wild and tended plants in rice-cultivated agroecosystems, compare this to botanical surveys, and analyze the extent to which ecosystem services contribute social-ecological resilience in the Terai Plains of Nepal. Method Sampling was carried out in four landscapes, 22 Village District Committees, and 40 wards in the monsoon season. Data collection was based on transects walks to collect plant specimens, structured and semi-structured interviews, and participatory fieldwork in and around home gardens, farms, and production landscapes. We asked 180 farmers to free-list vernacular names and describe use-value of wild and tended plants in rice-cultivated agroecosystems. Uses were categorized into eight broad groupings, and 61 biomedical ailment classifications. We assessed if knowledge of plant species diversity and abundance differed with regard to caste, age, and gender. Results Nepalese farmers have a deep knowledge of the use and management of the 391 vascular plant specimens identified, which provide key provisioning, regulating, supporting, and cultural ecosystem services. Altogether, plants belong to 76 distinct plant species from 49 phylogenetic families: 56 are used to cure 61 ailments, 27 for rituals, 25 for food, 20 for timber, 17 for fuel, 17 for fodder, 11 for soil enhancement, and eight for pesticides. Four caste groups have statistically different knowledge, and younger informants report a lower average number of useful plants. Conclusion Agricultural landscapes in Nepal are reservoirs of biodiversity. The knowledge of the use of wild and tended plant species in and around these farms differs by the caste and age group of land manager. Conducting research on agroecosystems will contribute to a deeper understanding of how nature is perceived by locals, to more efficient management and conservation of the breadbasket of Nepal, and to the conservation of valuable, but disappearing traditional knowledge and practice.